Large scale repository auditing to ISO 16363 - Rodrigues, Eloy (2014)
This paper describes an audit process carried out on 26 digital repositories according to the recently approved standard ISO16363 (Audit and Certification of Trustworthy Digital Repositories). The 26 repositories share a common infrastructure hosted by RCAAP (Open Access Scientific Repository from Portugal), a free hosting service provided to research institutions in Portugal. It addresses the process and the strategic alignment with the project objectives integrated with other developments related to digital preservation of institutional repositories. This work presents the first results of the analysis of the three topics: Organizational Infrastructure, Digital Object Management and Infrastructure and Security Risk Management.